Bond strength to micro-shearing in feldspathic ceramics conditioned with hydrofluoric acid and subjected to different removal times and methods - Peralta Mas, Fátima Brunella (2025)
Objective: To evaluate the micro-shearing bond strength in feldspathic ceramics through various methods of hydrofluoric acid residue removal and different application times. Materials and methods: An in vitro study in which 9% hydrofluoric acid was applied for 1 minute as a surface treatment on feldspathic ceramic discs. The samples were divided into 4 groups with 3 different application times and subjected to different removal methods: water and air spray; ultrasonic bath with distilled water; active application of 37% phosphoric acid for 1, 2, and 4 minutes; and a combination of 37% phosphoric acid actively applied for 1, 2, and 4 minutes followed by an ultrasonic bath with distilled water for 4 minutes. Cylinders of flowable resin were prepared and placed on the ceramic discs. Samples were subjected to micro-shear tests on a semi-universal testing machine. Results: The two-way ANOVA test and Tukey's post-hoc test (p < 0.05) revealed that the water spray group at 1 and 2 minutes, and the ultrasonic bath at 4 minutes showed the highest bond strength values ​​with a statistically significant difference. Conclusions: The water spray removal method for 1 and 2 minutes showed the highest bond strength value, while the lowest was observed with the 37% phosphoric acid removal method for 2 minutes.